2017
DOI: 10.1111/wrr.12585
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated epithelialization and improved wound healing metrics in porcine full‐thickness wounds transplanted with full‐thickness skin micrografts

Abstract: Split-thickness skin grafting (STSG) is the current gold standard for treatment of extensive burn and traumatic skin injuries. However, STSG is limited by donor-site morbidity and availability, and often leads to scarring and wound contracture. Furthermore, these thin grafts lack dermal elements such as nerves and adnexa which are important in recapitulating normal skin function. Methods of fractional skin replacement either as minced STSGs or microscopic skin tissue columns have been proposed, though these te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
0
16
2
Order By: Relevance
“…At this high harvest density, the native vascular tree may be damaged, yielding poor healing outcomes as the importance of an intact vascular tree prevents ischemia and allows for the migration of inflammatory and proliferative mediators, which are key to healing. 34 Though not previously reported in the literature, harvest density does indeed impact healing at the donor site, with previous reports of donor site healing around 1 week, and very little to no scarring visualised after 1 month, it's likely that these studies used a lower harvest density 12,13 We were able to compare this morbidity to the donor site data in our first objective, which was harvested at 7%-10%. At this harvest density, we saw 100% re-epithelialisation by day 7, faster than STSG donor sites, and less dyspigmentation compared to STSGs, visualised in Figure 5..…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…At this high harvest density, the native vascular tree may be damaged, yielding poor healing outcomes as the importance of an intact vascular tree prevents ischemia and allows for the migration of inflammatory and proliferative mediators, which are key to healing. 34 Though not previously reported in the literature, harvest density does indeed impact healing at the donor site, with previous reports of donor site healing around 1 week, and very little to no scarring visualised after 1 month, it's likely that these studies used a lower harvest density 12,13 We were able to compare this morbidity to the donor site data in our first objective, which was harvested at 7%-10%. At this harvest density, we saw 100% re-epithelialisation by day 7, faster than STSG donor sites, and less dyspigmentation compared to STSGs, visualised in Figure 5..…”
Section: Discussionmentioning
confidence: 73%
“…To our best knowledge, this present study was the first to examine the results of directly implanting FTSCs into small incisions made in the wound bed, albeit deep partial‐thickness burns, maintaining their natural orientation. The primary method to applying FTSCs to wound beds previously published involve a ‘scatter’ method, where skin columns are randomly laid onto a wound bed 12–14,29 . Results from this method thus far have been promising, showing increased re‐epithelialisation and less wound contraction compared to healing by secondary intent.…”
Section: Discussionmentioning
confidence: 99%
“…78 Similarly, in Yorkshire pigs, Rettinger et al, 2017, showed myofibroblast populations persist at Day 14 and Day 28 postwounding, although immunoreactivity for α-SMA was reduced by the addition of microscopic skin tissue columns. 80 Our own analysis of the healing of 2 cm diameter wounds in Yorkshire pigs found persistence of myofibroblasts at Day 28, although immunoreactivity was reduced compared to Day 7 (Figure 2). Yorkshire pigs, although they do persist in burns at this timepoint.…”
Section: Full Thicknessmentioning
confidence: 85%
“…Although autologous skin grafts are clinically proven to enhance wound healing, 11 all skin grafting techniques are implicated in some degree of donor site trauma. 18 Significant drawbacks of current harvesting techniques include pain at the donor site, limited donor skin availability, 19 scarring, and an inability to restore complete skin function and architecture. 12 There have been several attempts to reduce the trauma from donor site harvesting.…”
Section: Discussionmentioning
confidence: 99%